The Value of Friendship in Animated Films Masha and The Bear: Semiotic Review - Thera Widyastuti; Kiki Srimayanti (MEDIASI : Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2023)
Animated is one of the film genre that is used as a tool of education for children. One of the animated series that is popular in Indonesia is Masha and the Bear. The friendship that exists between Masha and the bear is closely related to each other. This research focuses on examining the story of Masha and the bear's friendship in the episode entitled "Hopefully Get Well Soon" and the episode "/Sweet Life". This study used descriptive qualitative method. The theory used is semiotics and friendship. The results of the research findings reveal the value of friendship between Masha and the bear in four components of friendship, namely familiarity in interaction, trust between each other, acceptance in attitude and social, and support provided by both parties in a friendly relationship.